ANALISIS SUMBER DAYA MANUSIA PENGELOLA DANA BANTUAN OPERASIONAL SEKOLAH (BOS) MADRASAH IBTIDAIYAH (MI) SWASTA KABUPATEN BATANG - Firkiya Khubasa; Dewi Erowati; Heri Wahyudi (Universitas Bina Taruna Gorontalo, 2024)
This study aims to analyze the quality of human resources who are the treasurer of the management of the School Operational Assistance (BOS) funds of Madrasah Ibtidaiyah Private Batang Regency in 2019. The research method is qualitative descriptive. The data analysis techniques used are data reduction, data presentation, and conclusion drawn. The results of the study show that the quality of the treasurer of the BOS fund management as a whole after experiencing improvement is good, although in its implementation there are some that have poor results and there are obstacles described as follows: a) The planning for the management of BOS funds is carried out well according to Juknis, but the participation of student guardians is still minimal. b) The allocation of BOS funds that are not in accordance with the number of students, the number is limited and there is a delay in the implementation of BOS fund management. c) The implementation of BOS fund management is mostly good, although it is constrained because some treasurers are not able to manage BOS funds administratively. d) The BOS fund accountability report has been implemented according to the guidelines. e) Control activities are carried out properly by the authorities. f) Quality improvement activities are carried out well. Furthermore, the factors that affect the quality of the treasurer of BOS fund management are: a) Organizational commitment factor. b) Work environment factors.